Genesis of Urban R E Co-operative Credit - ACS Books (Genesis of Urban Co-operative Credit in India : (ISBN - 978-93-94893-00-9), 2022)
An Indian peasant lives in debt, dies in debt and also passes a portion of it, to the future  generation to pay off. Similar words were  used by the Royal Commission on Agriculture in  1929 which are true even today, in the agricultural  sector despite more than seven decades of our  independence. The co-operative movement  especially the co-operative credit sector emerged  due to sustained efforts made by the British Civil  servants in the pre-independence period and the  desire to use them as a tool for socio-economic  transformation of the rural sector in the post independence period.